Examining the Impact of Peer and Family Belongingness on the Career Decision-making Difficulties of Young Adults: A Path Analytic Approach. (February 2014) - Slaten, Christopher D.; Baskin, Thomas W.
Career decision making continues to be a major area of research, particularly related to the factors that influence the construct. The purpose of this study was to examine a hypothesized model predicting the relationships between career decision-making difficulties and perceived belongingness, specifically peer and family belongingness. Participants included 436 undergraduates, who completed measures of belongingness, psychological distress, academic motivation, and career decision-making difficulties. The researchers conjectured that peer and family belongingness would each be indirectly associated with career decision-making difficulties as mediated by academic motivation and psychological distress. Overall, fit indices supported the hypothesized model but indicated different outcomes for family and peer belongingness. Family belongingness was significantly related to career decision-making difficulties, while peer belonging was not significantly associated to any variable in the hypothesized model. Practical implications are discussed, along with suggestions for future research.